If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7y + -2 + 2y = 79 Reorder the terms: -2 + 7y + 2y = 79 Combine like terms: 7y + 2y = 9y -2 + 9y = 79 Solving -2 + 9y = 79 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 9y = 79 + 2 Combine like terms: -2 + 2 = 0 0 + 9y = 79 + 2 9y = 79 + 2 Combine like terms: 79 + 2 = 81 9y = 81 Divide each side by '9'. y = 9 Simplifying y = 9
| n/6-24=-5 | | 5a-5+5a= | | N+20=-48 | | (8y+4)+(4y+8)=5y-9 | | 15x(y-2)= | | 15x(y-2)=40 | | -72=6x-3(-7x-21) | | -16t^2+22t+22=0 | | 9x+2=15x | | 1/4+3/4t=10 | | 1.3x-2.39=5.76x+4.47 | | 7x^3+22x^2+17x+2=0 | | 2x+3y=79 | | 7500=x*.5+x*.5 | | 1/6f+3/4=1/2 | | 2x+39b=14+3b | | 2v-6=-2v+6+7-3 | | 6(-3-7)= | | X+(x*0.087)=y | | 9y+6(4y-3)=5(y-7) | | 32w^2+32w+8=0 | | 1/3w9 | | 6u+8v-7-6u-4v+8w= | | -4(1+b)+8b=-14+2b | | -192=8(4x-8) | | x^2=x-57 | | 15/50=3x | | 5x(x+3)+6(x+3)= | | 6(k+7)=18+2k | | -9/4=r-4/5 | | 8x+4(x-7)=3(8-x)+12 | | 3c+7+12c=53 |